Role of ptsO in Carbon-Mediated Inhibition of the Pu Promoter Belonging to the pWW0 Pseudomonas putida Plasmid - Cases, Ildefonso (American Society for Microbiology, 2001)
An investigation was made into the role of the ptsO gene in carbon source inhibition of the Pu promoter belonging to the Pseudomonas putida upper TOL (toluene degradation) operon. ptsO is coexpressed with ptsN, the loss of which is known to render Pu unresponsive to glucose. Both ptsN and ptsO, coding for the phosphoenolpyruvate:sugar phosphotransferase system (PTS) family proteins IIA(Ntr) and NPr, respectively, have been mapped adjacent to the rpoN gene of P. putida. The roles of these two genes in the responses of Pu to glucose were monitored by lacZ reporter technology with a P. putida strain engineered with all regulatory elements in monocopy gene dosage. In cells lacking ptsO, Pu activity seemed to be inhibited even in the absence of glucose. A functional relationship with ptsN was revealed by the phenotype of a double ptsN ptsO mutant that was equivalent to the phenotype of a mutant with a single ptsN disruption. Moreover, phosphorylation of the product of ptsO seemed to be required for C inhibition of Pu, since an H15A change in the NPr sequence that prevents phosphorylation of this conserved amino acid residue did not restore the wild-type phenotype. A genomic search for proteins able to phosphorylate ptsO revealed the presence of two open reading frames, designated ptsP and mtp, with the potential to encode PTS type I enzymes in P. putida. However, neither an insertion in ptsP nor an insertion in mtp resulted in a detectable change in inhibition of Pu by glucose. These results indicate that some PTS proteins have regulatory functions in P. putida that are independent of their recognized role in sugar transport in other bacteria.